Waste Pricing Based On Costs - Netseva–Porcheva, Tatyana; Urucheva, Daniela (Research Papers, 2019)
The aim of the paper is to present a cost accounting model related to the management of wastes such as paper, plastic, wood and glass, which model to be used in their pricing. The paper clarifies the specificity of the waste pricing process, reveals the significance of the full cost analysis in waste pricing, presents a model of how to perform cost analysis and an author model of grouping the activities in stages with regards to the waste management process.
Keywords: Pricing; Waste; Costs